2019
DOI: 10.1111/pcn.12812
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of repetitive transcranial magnetic stimulation on modified 2010 criteria‐diagnosed fibromyalgia: Pilot study

Abstract: Aim Fibromyalgia is often comorbid with depression, and less than half those patients achieve satisfactory improvement after adequate pharmacological intervention. The investigation of repetitive transcranial magnetic stimulation (rTMS) at left dorsolateral prefrontal cortex for modified‐2010 American College of Rheumatology (ACR) fibromyalgia and major depressive disorder (MDD) is still in its infancy. Methods In this double‐blind, randomized, sham‐control study, subjects diagnosed with ACR‐2010 fibromyalgia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…A similar effect was found when the invasive chronic motor cortex stimulation decreased the thalamic hyperactivity in patients with thalamic pain (Tsubokawa et al, 1993). Aligned with this assumption, we found extensive literature showing that the transcranial stimulation (i.e., tDCS and TMS) might improve the disrupted neurochemical processes in chronic pain (Cheng et al, 2010).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A similar effect was found when the invasive chronic motor cortex stimulation decreased the thalamic hyperactivity in patients with thalamic pain (Tsubokawa et al, 1993). Aligned with this assumption, we found extensive literature showing that the transcranial stimulation (i.e., tDCS and TMS) might improve the disrupted neurochemical processes in chronic pain (Cheng et al, 2010).…”
Section: Discussionmentioning
confidence: 65%
“…Besides, it can help to personalize the therapeutic approach. Despite the absence of a FDA-approved neuromodulation protocol targeted to patients with comorbidity MDD and FM, the effectiveness of neuromodulatory techniques (i.e., tDCS and TMS) has been supported by consistent evidence to treat both FM and depression (Kauffmann et al, 2004; Antal et al, 2010; Brunoni et al, 2011; Marie, 2014; Fagerlund et al, 2015; Castillo-Saavedra et al, 2016; Cheng et al, 2018; Karina do Monte-Silva et al, 2019). Considering that these two disorders are frequently overlapped, it poses a considerable challenge to decide if it would be better to stimulate the M1 or the dorsal lateral prefrontal cortex for the treatment of pain accompanied by depression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the decrease in VAS scores was significantly prominent in patients who received M1 rTMS stimulation, whereas improvement in physical function was significant in patients who received DLPFC rTMS stimulation. A similar RCT was performed in the same year by Cheng et al (61) that included 20 patients with FM who also had major depressive disorder (MDD). This study showed that pain was significantly improved in patients who received 10-Hz rTMS over the left DLPFC (nine patients) over 2 weeks as compared with that in patients who received sham stimulations (11 patients).…”
Section: Fibromyalgiamentioning
confidence: 99%
“…The initial search returned 455 articles. Eighteen RCTs [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] with 643 participants entered qualitative synthesis (Figure 1). Two studies [11,18] included two intervention arms; therefore, the control groups for this research were divided for separate comparisons, creating 20 comparisons in total.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) have reported that rTMS can alleviate fibromyalgiarelated symptoms with few adverse events [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Although the mechanism of action of rTMS in fibromyalgia is not fully understood yet, it is believed to modulate the brain areas associated with affective-emotional components of pain, as well as activating the endogenous opioid analgesic system through mediating the motor cortex [28].…”
Section: Introductionmentioning
confidence: 99%